Literatur Review Hubungan Perubahan Iklim dengan Transmisi Malaria di Wilayah Tropis - Teuku Nazarullah; Ekasusanti Ekasusanti; Massatriadi Massatriadi; Radhiah Zakaria (Pelantar Press, 2026)
DDengue hemorrhagic fever (DHF) remains a significant public health problem in tropical and subtropical regions, with its incidence strongly influenced by environmental factors, particularly climate. Variations in rainfall, temperature, and humidity are known to affect the population dynamics of the Aedes aegypti mosquito and the transmission patterns of the dengue virus. This study aims to review and analyze scientific evidence regarding the relationship between climatic factors namely rainfall, temperature, and humidity and the incidence of dengue based on findings from previous studies. The method used was a literature review of several national and international journals published in recent years, encompassing various research designs such as time series studies, ecological studies, cross-sectional surveys, and modeling studies. The review results indicate that rainfall and humidity are the most consistently significant climatic factors associated with increased dengue incidence across different regions, as they contribute to the creation of mosquito breeding sites and enhance vector survival. Temperature also influences dengue incidence by accelerating the mosquito life cycle and dengue virus replication, although the strength of this association varies by location and time period. Modeling studies further project that climate change may substantially increase the dengue burden in the future. In conclusion, rainfall, temperature, and humidity are important and interrelated climatic factors influencing dengue incidence, and therefore should be comprehensively considered in early warning systems as well as in dengue prevention and control strategies.